2019
DOI: 10.1111/jcmm.14566
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of tumour necrosis factor alpha regulates hypocretin (orexin) expression, sleep and behaviour

Abstract: Hypocretin 1 and hypocretin 2 (orexin A and B) regulate sleep, wakefulness and emotion. Tumour necrosis factor alpha (TNF‐α) is an important neuroinflammation mediator. Here, we examined the effects of TNF‐α treatment on hypocretin expression in vivo and behaviour in mice. TNF‐α decreased hypocretin 1 and hypocretin 2 expression in a dose‐dependent manner in cultured hypothalamic neurons. TNF‐α decreased mRNA stability of prepro‐hypocretin, the single precursor of hypocretin 1 and hypocretin 2. Mice challenged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 66 publications
(156 reference statements)
0
9
0
Order By: Relevance
“…Immune systems have long been implicated in the mechanism of narcolepsy 31 , but recent evidence suggests that neuroinflammation is involved in the development of ADHD as well 32 . Furthermore, neuronal inflammation has been shown to not only alter levels of monoamine neurotransmitters, including dopamine and noradrenaline 32 but also to affect the expression of histamine and orexin 33 , 34 , which are promising targets for novel drug treatments for narcolepsy. In addition, gene-sets relevant to glial cell function and iron transport were found to be associated with both ADHD traits and narcolepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Immune systems have long been implicated in the mechanism of narcolepsy 31 , but recent evidence suggests that neuroinflammation is involved in the development of ADHD as well 32 . Furthermore, neuronal inflammation has been shown to not only alter levels of monoamine neurotransmitters, including dopamine and noradrenaline 32 but also to affect the expression of histamine and orexin 33 , 34 , which are promising targets for novel drug treatments for narcolepsy. In addition, gene-sets relevant to glial cell function and iron transport were found to be associated with both ADHD traits and narcolepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that TNF-a level is increased in AD patients and that inhibition of TNF-a is proposed to treat AD patients. 35,36 In this study, oxidative stress markers and TNF-a were ameliorated in sildenafil-treated rats, reflecting its antioxidant and anti-inflammatory effect, matching with previous studies reported that cGMP accumulation, via PDE 5 inhibtion by sildenafil, inhibited the neuronal inflammation, by blocking the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) and decreased the level of proinflammatory cytokines of IFN-g, TNF-a, IL-1b, IL-2 and cycloxygenase-2. 37,38 Based on the universal effect of vascular dysfunction and inflammation in cognitive decline and neurodegeneration observed in AD patients, 39 the present study reported the effect of sildenafil on VCAM-1 and VEGF-A production and their relation to a-synuclein deposition and nestin expression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that TNF-α level is increased in AD patients and that inhibition of TNF-α is proposed to treat AD patients. 35,36…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine hydroxylase (TH), a key enzyme for DA biosynthesis, is decreased in PD, which is a hallmark in the progression of PD [9,10]. Interestingly, it was reported that the loss of dopaminergic neurons resulted from apoptosis, necrosis and autophagy in PD [11][12][13]. However, there is no unified definite theory to explain the cause of loss of dopaminergic neurons.…”
Section: Introductionmentioning
confidence: 99%